Vaccinia virus antibodies in calves submitted to experimental infection - Schatzmayr, Hermann G.; Denne, Yone e Silva (Pesquisa Agropecuaria Brasileira, 2014)
Antibody formation for Vaccinia virus, after inoculation in calves, used for Smallpox vaccine preparation, have been tested. Complement-fixing, hemagglutination inhibition, neutralizing and precipitating antibodies have been demonstrated. The globulin class of these antibodies has also been determined after gel filtration in Sephadex G-200. A fast antibody formation in the animals has been observed like the one observed in human re-vaccination and faster than that observed in the human prime vaccination. The pattern observed on formation and decrease of globulins IgM suggest its use in the diagnosis of recent infections by Pox viruses. This is particularly important in order to make a differential diagnosis with other vesicular virus infections and older infections or vaccinations with members of Pox viruses group.